The determinants of Indonesia's business cycle - Berry A. Harahap; Pakasa Bary; Anggita Cinditya M. Kusuma (Journal of Central Banking Theory and Practice, 2020)
This study investigates the determinants of Indonesian's business cycle using the global vector autoregressive (GVAR) approach, by including spillover responses within 33 countries with 2000 bootstrap replications. The results show that Indonesia's business cycle is influenced by both domestic and external factors. In addition to exogenous shocks from output, the dominant domestic factors are monetary policy and price competitiveness. The dominant external factors are global economic activity and liquidity conditions, particularly those originating from the Chinese economy. Spillovers from a number of economies appear to shape Indonesia's economic fluctuations. The paper discusses such relevant spillovers.
Keywords: E32; F44; E30; C22; 330; Business cycle; Trade relations; Global vector autogressive approach